Glycosphingolipids from Magnaporthe grisea cells: expression of a ceramide dihexoside presenting phytosphingosine as the long-chain base. - Maciel, D; Rodrigues, M; Wait, R; Villas Boas, M; Tischer, C; Barreto-Bergter, E (2002)
Magnaporthe grisea is a fungal pathogen that infects rice leaves and causes rice blast, a devastating crop disease. M. grisea produces active elicitors of the hypersensitive response in rice that were previously identified as ceramide monohexosides (CMHs). Using several chromatographic approaches, mass spectrometry, and nuclear magnetic resonance, we identified ceramide mono- and dihexosides (CDH) in purified lipid extracts from M. grisea cells. As described by other authors, CMH consists of a ceramide moiety containing 9-methyl-4,8-sphingadienine in amidic linkage to 2-hydroxyoctadecenoic or 2-hydroxyhexadecenoic acids and a carbohydrate segment consisting of one residue of glucose. CDHs, however, contain beta-galactose (1-->4)-linked to beta-glucose as sugar units and phytosphingosine as the long-chain base, bound to a C24 alpha-hydroxylated fatty acid. To our knowledge, this is the first report on the occurrence of CDH in a fungal species and illustrates the existence of an alternative path of ceramide glycosylation in fungal cells.